Relevance of Piaget's cognitive principles among 4-7 years old children: A descriptive cross-sectional study - Sharath Asokan; Sharmila Surendran; Sureetha Asokan; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2014)
Background: According to Jean Piaget, children between 4 and 7 years of age are under the intuitive sub-stage of preoperational stage. Children possess specific characteristics based on their age. These characteristic cognitive principles have not been assessed in a dental setting. Research on the cognitive development of the child and its application to dental health care can enable pediatric dentists to better understand, approach and deliver improved quality of care to children. Purpose: The purpose of this study is to assess the prevalence of Piaget's cognitive principles among preoperational children. Materials and Methods: This cross-sectional study was conducted among 200 children, aged 4-7 years. Various characteristics, specific for this age group, such as egocentrism, concept of cardinal numbers based on centration, lack of conservation, and reversibility were assessed, using three tangible experiments and two interview questions. A comparison of the prevalence of each character was carried out among the children based on their age. Results: The prevalence of egocentrism based on the three mountain experiment was 65% and the personal interview showed a prevalence of 58%. Centration was appreciated in 83% of the study sample. The beaker experiment and the interview question revealed a lack of conservation in 89% and 59% of the children, respectively. There was a gradual and uniform reduction in the prevalence of the characters with an increase in age. Conclusion: All the three features assessed were observed in most of the children between 4 and 7 years of age as described by Piaget and most of his principles still appear valid today.